Reconstructive Rhinoplasty: New Technique of Central Cartilaginous Support - Sajid, Muhammad; Bhatti, Zahid; Nazeer, Aisha; Mughese, Sadia; Tayyaba, Tayyaba; Amin, Mohammad Mughese (Jurnal Plastik Rekonstruksi, 2013)
Background: Honour amputation is a common cause of nose amputation in Pakistan, especially in dahawalpur region. Skeletal support is always a problem in major nasal amputations. It needs multiple delays and extra support later on, with all traditional techniques. Patient and Method: We reported three cases of amputation of the nose. We used sliding septal technique to reconstruct the central cartilaginous support of the nose. In this technique we used the remaining septum as a free graft. Ten patients were treated with this technique with excellent results. Nasal lining was provided either with septal artery mucosal flap or with nasolabial flap. Forehead flap was the only flap to provide external cover. Nostril rim were grafted with trimmed choncial cartilage primarily. In three patients debulking procedures were done later on , but no skeletal procedures. Result: This technique has given an excellent skeletal support and a nice tip projection with no delays or extra support later on. Patient satisfaction rate was 100%. Summary: Sliding septal technique is a very reliables, cost effective technique. It provides an excellent tip support in a single procedure, without sacrificing other precious material like rib or bone.